Status and distribution of humpback whales (Megaptera novaeangliae) in northern Luzon, Philippines - Acebes, Jo Marie V.; Darling, J. D.; Yamaguchi, Manami (J. Cetacean Res. Manage., 2023)
Since the verification of the occurrence of humpback whales in the Babuyan Islands, Philippines in 1999, studies have been carried out on their status and distribution. Boat-based surveys of the waters around the islands were conducted from 2000-03. In 2003, a survey was also conducted off the eastern coast of Northern Sierra Madre. Once the whales were sighted, the location, group composition and behaviour were noted, fluke photo-identifications taken, sloughed skin and biopsy samples collected and songs recorded. A total of 367 humpback whale sightings were documented in four seasons around the Babuyan Islands. However, a cow-calf pair sighting off the coast of Northern Sierra Madre indicates that this breeding area may extend farther south. A total of 69 individuals have been photo-identified from 1999- 2003. Re-sightings across years are as follows: one individual was sighted for three consecutive years (2001-03); two individuals for two consecutive years (2001-02 and 2002-03); while three individuals were sighted in two different years (1999 and 2002; 2001 and 2003). Twelve of the 40 individuals photo-identified in the Philippines from 1999-2002 were matched to humpback whales identified in Ogasawara and Okinawa, Japan, including one whale that moved between these regions in one season. These matches indicate that the Philippine humpback whales are part of this greater western Pacific population. A subjective comparison between humpback whale songs recorded in the Philippines and Hawaii in 2002 indicated marked similarities. A total of nine distinctive themes were identified; seven of these were common to songs from both regions. The similarity in songs suggests humpback whales in the Philippines mix to some degree, at least acoustically, with the whales in Hawaii and the rest of the Pacific basin.